Implementasi CMS Pada Media Pembelajaran Mengenal Alat Musik Tradisional Indonesia - Sinduningrum, Estu; Suhendra, Renadi Fadino; Kamayani, Mia (MULTINETICS, 2018)
Traditional musical instruments were born and developed throughout the archipelago in Indonesia, which is still a hereditary habit in the community to date. This musical instrument is spread in almost all corners of the country and each region has different characteristics. Children in learning and knowing traditional musical instruments are less desirable because traditional musical instruments are considered outdated and old-fashioned, so they are reluctant to learn them. children are made media to introduce traditional CMS-based musical instruments and musical instruments made in 3D, so children want to know and learn traditional musical instruments. System modeling on the construction of this CMS use UML (Unified Modelling Language) with tool activity diagram, use case, class diagram and developed using the method waterfall which is run on system. System testing is permormed using alpha testing and beta testing, for beta testing is done by distributing the system testing questionnaire to the 15 listed respondent. For the result of the percentage is 86,67%, which means the result of this CMS assessment can be categorized very well.